INSTRUMENTS OF GOVERNANCE IN THE INDIGENOUS USAKEDET SOCIETY, 1895 – 1977 - EDET EFIONG OKON (International Studies Journal)
Before the advent of the colonial instrument of courts and Christianity, Usakedet people have developed home-made methods and instruments of indigenous administration of their society with the consciousness that no society could thrive in lawlessness, injustice and poor social standards. Also, the sustenance and maintenance of law and orders with the intention to impact the people’s ways of life for the purposesof nation-building, development and protection of the society from both external and internal attacks, constant communication with the ancestors and socio-ethical trainings. This study examines the unsung innovative attempts by the Usakedet traditional society to evolve indigenous method of governance. The studymade use of the primary and secondary evidencesnoting that Usakedet’s nation-building would have been more formidably globalized but for colonial incursion.